Early experience of laparoscopic varicocelectomy in College of Medical Sciences, Teaching Hospital, Bhartpur, Nepal - Agarwal, A; Sigdel, G; Lamichhane, N; Belokar, WK (Journal of College of Medical Sciences-Nepal, 2012)
Varicocele is dilatation of pampiniform plexus of veins in the scrotum. Laparoscopic varicocelectomy is gaining popularity since its introduction in 1990s. We present our experience of laparoscopic varicocelectomy in College of Medical sciences, Teaching Hospital, Bharatpur, Nepal. Ten patients underwent laparoscopic varicocelectomy between Jan 2009 to July 2010. The mean age of patients was 25.7 (range, 14 to 38) years. All varicoceles were detected clinically and confirmed by scrotal color Doppler ultrasonography. The varicocele was left sided in 6 (60%) and bilateral in 4 cases(40%). The surgical indications were scrotal pain and discomfort in 8, infertility in 1, and both in 1. Mean operation time was 50 ± 22 minutes (range, 35-110). Following operation 6 patients were symptom free immediately and remaining 2 patients also became asymptomatic on 15 days followup. Both patients of infertility, lost follow up, post operatively. Neither recurrent varicocele nor hydrocele was detected with a mean follow-up of 13 months. All patients were discharged within 24 hours postoperatively. Every attempt was made to preserve spermatic artery and lymphatic vessel. The procedure is safe and effective. Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-2, 32-36 DOI: http://dx.doi.org/10.3126/jcmsn.v8i2.6835